Penggunaan Solar Collector Sebagai Pemanas Awal Air Masuk dan Pemanas Tambahan Bawah Heat Absorber Pada Basin Solar Still Untuk Meningkatkan Efisiensi - Effendi, M. Syafwansyah; Hendrawan, Ahmad; Rahman, Noor (P3M Politeknik Negeri Banjarmasin, 2016)
All basin solar still in general use under the askew glass cover as condensation media toplace the condensate flows toward the lower sections with use gravitation. It is known thatwhen condensation occurs release considerable heat energy to environment. Solve thisproblem, in this research is to minimize the loss of substantial energy, utilizing the heat fromthe solar collector. Heat is supplied to the bottom of the heat absorber and heat exchanger.Research methods is experiment. In this research is examine both the prototype, that is basinsolar still with solar collector and basin solar still without solar collector. The measuredparameter is temperature button section heat absorber, outside heat absorber, buttonsection of glass cover, condensate water, environment, solar collector, heat exchanger andsoar radiation.In this result temperature average at button section heat absorber is 47,03oC for prototypewith solar collector and without solar collector is 45,25oC. Solar radiation average is 304,11W/m2. Efficiency both prototype is 29,45% with solar collector and 19,86% without solarcollector. By comparing efficiency two prototype is concluded that the Solar Collector aspreheater water and additional heating of water under heat absorber 67.45% better than thatwithout using Solar Collector.